2008
DOI: 10.1161/hypertensionaha.107.105247
|View full text |Cite
|
Sign up to set email alerts
|

Systematic, Genome-Wide, Sex-Specific Linkage of Cardiovascular Traits in French Canadians

Abstract: Abstract-The sexual dimorphism of cardiovascular traits, as well as susceptibility to a variety of related diseases, has long been recognized, yet their sex-specific genomic determinants are largely unknown. We systematically assessed the sex-specific heritability and linkage of 539 hemodynamic, metabolic, anthropometric, and humoral traits in 120 French-Canadian families from the Saguenay-Lac-St-Jean region of Quebec, Canada. We performed multipoint linkage analysis using microsatellite markers followed by pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 52 publications
3
33
0
Order By: Relevance
“…We have previously described that a significant portion of cardiometabolic phenotypes has a sex-dependent penetrance in families with hypertension on Quebec founder population. 35 Regardless, the sex difference in the BP phenotype of the KO mice is true and significant, according to analysis with a mixed-effects linear model (Figure 2c). Nakayama et al 36 reported that smooth muscle-specific deletion of EFNB2 using SM22Δ-Cre results in lower body weight, reduced VSMC proliferation, thinner arterial vessel wall and enlarged arterial diameter.…”
Section: Discussionmentioning
confidence: 94%
“…We have previously described that a significant portion of cardiometabolic phenotypes has a sex-dependent penetrance in families with hypertension on Quebec founder population. 35 Regardless, the sex difference in the BP phenotype of the KO mice is true and significant, according to analysis with a mixed-effects linear model (Figure 2c). Nakayama et al 36 reported that smooth muscle-specific deletion of EFNB2 using SM22Δ-Cre results in lower body weight, reduced VSMC proliferation, thinner arterial vessel wall and enlarged arterial diameter.…”
Section: Discussionmentioning
confidence: 94%
“…29 This FTO SNP is a SNP on the array that is closest to the FTO SNP genotyped in adolescents. The rs9302652 genotype distribution in the adult cohort was following: CC, 9.7%; CT, 40.6%; and TT, 49.7%.…”
Section: Adultsmentioning
confidence: 99%
“…[1][2][3][4][5] The high heritability of gene expression variation indicates that it may serve as an intermediate phenotype for the identification of genomic determinants of complex traits, such as essential hypertension. We initiated this approach by exploring the pleiotropic regulation of heat stress genes mapping the mRNA accumulation after heat stress and using recombinant inbred strains (RIS) developed by inbreeding the F 2 generation of normotensive Brown-Norway (BN-Lx) and spontaneously hypertensive rats (SHR).…”
mentioning
confidence: 99%